Employing Qualitative Assessment to Identify Individual with Motor Difficulties - Ibrahim, Halijah; Zainuddin, Zainal Abidin (2005)
Investigation in identifying individual with motor difficulties in Adapted Physical Education among Malaysian young adolescents is unknown and has not been documented. Somehow, the awareness on the incidence of motor difficulties, commonly called Developmental Coordination Disorder is low. Therefore, data has been collected to explore motor ability level.